The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12094-017-1736-9
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of prostate-specific membrane antigen positron emission tomography(PSMA PET/CT)-guided radiotherapy in oligometastatic prostate cancer patients

Abstract: By providing optimal LC, low toxicity and a promising PFS in CS patients, the current retrospective study illustrated that Ga PSMA PET-CT-guided RT may be an attractive treatment strategy in patients with oligometastatic prostate cancer. Validation by randomized trials is eagerly awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
3
29
1
Order By: Relevance
“…This was in line with the results of Guler and Henkenberens et al 23,24 who found similar levels of PSA response to MDT in OPCa diagnosed by PSMA-PET/CT. 23,24 However, in the study of Guler et al 23 all patients also had ADT throughout treatment and in the study of Henkenberens et al 24 patients with bone metastases continued ADT during and after radiotherapy. 23,24 Considering that 8 of 20 patients (40%) in our present study also received ADT during and after RT, we analyzed the PSA response separately in the subgroup with (n=8) and without (n=12) additional ADT (Figure 2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was in line with the results of Guler and Henkenberens et al 23,24 who found similar levels of PSA response to MDT in OPCa diagnosed by PSMA-PET/CT. 23,24 However, in the study of Guler et al 23 all patients also had ADT throughout treatment and in the study of Henkenberens et al 24 patients with bone metastases continued ADT during and after radiotherapy. 23,24 Considering that 8 of 20 patients (40%) in our present study also received ADT during and after RT, we analyzed the PSA response separately in the subgroup with (n=8) and without (n=12) additional ADT (Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…22 Nevertheless, to our knowledge, only few studies have investigated the efficacy of MDT based on PSMA-PET/CT-imaging in OPCa. [23][24][25] In our present retrospective study on PSMA-PET/CT-guided RT as MDT, we found a significant decrease in PSA levels of median 1.47ng/ml prior to RT down to median 0.20ng/ml at last follow up (p<0.001). This was in line with the results of Guler and Henkenberens et al 23,24 who found similar levels of PSA response to MDT in OPCa diagnosed by PSMA-PET/CT.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The use of image-guided, metastasis-directed ablative therapy (such as stereotactic body radiation therapy) to distant lesions is an attractive strategy (35)(36)(37)(38) being investigated in prospective trials (NCT01558427, NCT02274779) (39,40). The success of this approach, however, depends on accurate staging.…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains unclear if oligoprogressive CRPC patients represent a distinct biological entity or whether the PSMA-positive lesions are just a snapshot of a systemic disease, the improved sensitivity resulting in an earlier detection and the 3D localization of oligoprogressive disease may offer a window of opportunity. In the study of Guler et al, 10 CRPC patients treated with intensitymodulated and image-guided radiotherapy showed a progression free survival (PFS) of 0% at 12 months[40]. Similarly Muldermanns et al reported a biochemical PFS of 54% and a distant PFS of 45 % at 16 months[39].…”
mentioning
confidence: 96%